Surgical anatomy & techniques to the spine. - Kim, Daniel H (ClinicalKey., 2006)
Written by three neurosurgeons and an orthopedic surgeon, this comprehensive reference's multidisciplinary approach makes it relevant and informative to all surgeons regardless of their specialty or level of surgical experience. After thoroughly reviewing the anatomy and approaches to the spine, the authors lead you through a full range of state-of-the-art techniques in spine surgery, including those procedures commonly performed for degenerative disease, trauma, scoliosis, tumor, and infection. Abundant full-color illustrations, three-dimensional images and cadaver dissection photos walk you through both simple and complex spinal surgical procedures. The bonus CD-ROM contains all the images from the book, including some of the most sought-after anatomic photographs and radiographic images in neurosurgery, brought together for the first time uniquely for this volume. Multiple-viewpoint, full-color photographs and illustrations provide a thorough presentation of procedures and relevant anatomy. Concise, atlas-style format makes techniques easy to understand and reproduce. The Bonus CD-ROM includes all the images from the book in an easily searchable format for use in electronic presentations. Multidisciplinary coverage makes the book relevant and informative to all spine surgeons. Facilitates diagnosis and complication avoidance with clinical pearls and hints.